Cross-species microbial genome transfer: a Review - Zhu, Mei-Chen; Cui, You-Zhi; Wang, Jun-Yi; Xu, Hui; Li, Bing-Zhi; Yuan, Ying-Jin (Frontiers in Bioengineering and Biotechnology, 2023)
Synthetic biology combines the various disciplines of biology, chemistry, information science, and engineering, and has multiple applications in biomedicine, bioenergy, environmental studies, and other fields. Synthetic genomics is an important area of synthetic biology, and mainly includes genome design, synthesis, assembly, and transfer. Genome transfer technology has played an enormous role in the development of synthetic genomics, allowing the installation of natural or synthetic genomics in a cellular environment that is easily modified to the genome. A more comprehensive understanding of genome transfer technology can help to extend its applications to other microorganisms. Here, we summarize the three host platforms for microbial genome transfer, review the recent advances that have been made in genome transfer technology, and discuss the obstacles and prospects for the development of genome transfer.